Integrated management of charcoal rot disease in susceptible genotypes of mungbean with soil application of micronutrient zinc and green manure (prickly sesban) - Shoaib, Amna; Khan, Kashif Ali; Awan, Zoia Arshad; Jan, Basit Latief; Kaushik, Prashant (Frontiers in Microbiology, 2022)
Charcoal rot disease incited by soil-borne fungus Macrophomina phaseolina (Tassi) Goid is a challenging disease due to the high and long-term persistence of fungus in the soil. This study assessed the potential of micronutrient zinc (Zn) and green manure (Sesbania bispinosa L.) in solitary and bilateral combinations to alleviate infection stress incited by M. phaseolina by improving plant productivity. A completely randomized design experiment was conducted in potted soil, artificially inoculated with a pathogen, sown with mungbean genotypes. Plants were analyzed for disease, growth, physiology and yield attributes. Concealment of plant re-sistance by M. phaseolina was recorded due to the imbalance production of antioxidant en-zymes, which also reduced plant vegetative and yield-related attributes. The heat map and principal component analysis based on 19 measured attributes with 16 treatments separated 2% green manure combined with Zn (2.44 or 5 mg/Kg) as the best treatment for alleviating charcoal rot disease, improving plant growth (length and biomass), physic-biochemical traits (photosynthetic pigment, total protein content, activity of superoxide dismutase, catalase, pe-roxidase, polyphenol oxidase), yield and biological attributes to an extent to lucrative farming in terms of harvest index (HI) and benefit-cost ratio (BCR).